Physiological and biochemical characteristics of boscalid resistant isolates of Sclerotinia sclerotiorum from asparagus lettuce - Dong-ya SHI; Feng-jie LI; Zhi-hui ZHANG; Qiao-nan XU; Ying-ying CAO; Jane Ifunanya MBADIANYA; Xin LI; Jin WANG; Chang-jun CHEN (Journal of Integrative Agriculture, 2023)
Laboratory mutants of Sclerotinia sclerotiorum (Lib) de Bary, resistant to boscalid, have been extensively characterized. However, the resistance situation in the lettuce field remains largely elusive. In this study, among the 172 S. sclerotiorum isolates collected from asparagus lettuce field in Jiangsu Province, China, 132 isolates (76.74%) exhibited low-level resistance to boscalid (BosLR), with a discriminatory dose of 5 μg mL−1. In comparison to the boscalid-sensitive (BosS) isolates, most BosLR isolates demonstrated a slightly superior biological fitness, as evidenced by data on mycelial growth, sclerotium production and pathogenicity. Moreover, most BosLR isolates showed comparable levels of oxalic acid (OA) accumulation, increased exopolysaccharide (EPS) content and reduced membrane permeability when compared to the BosS isolates. Nevertheless, their responses to distinct stress factors diverged significantly. Furthermore, the effectiveness of boscalid in controlling BosLR isolates on radish was diminished compared to its efficacy on BosS isolates. Genetic mutations were identified in the SDH genes of BosLR isolates, revealing the existence of three resistant genotypes: I (A11V at SDHB, SDHBA11V), II (Q38R at SDHC, SDHCQ38R) and III (SDHBA11V+SDHCQ38R). Importantly, no cross-resistance was observed between boscalid and other fungicides such as thifluzamide, pydiflumetofen, fluazinam, or tebuconazole. Our molecular docking analysis indicated that the docking total score (DTS) of the type I resistant isolates (1.3993) was lower than that of the sensitive isolates (1.7499), implying a reduced affinity between SDHB and boscalid as a potential mechanism underlying the boscalid resistance in S. sclerotiorum. These findings contribute to an enhanced comprehension of boscalid’s mode of action and furnish valuable insights into the management of boscalid resistance.